Comparative Study of Management of Open Proximal Metaphyseo-Diaphyseal Tibial Fractures by the Fire Arm and the Road Traffic Injuries Treated with Ilizarov - MUHAMMAD HANIF RAZA ELAHI RANA, MUHAMMAD KHALID SYED (Journal of Fatima Jinnah Medical University, 2018)
The objective of this study was to compare the results of open proximal metaphyseo-diaphyseal tibial shaft fractures secondary to high energy road side accident and firearm injury in adults fixed with Ilizarov system in two respective groups (A and B) in terms of union, complications and functional status of the patients.A descriptive cross-sectional study of 30 clinical cases of open proximal metaphyseo-diaphyseal tibial shaft fractures was conducted in Department of Orthopedic Surgery Mayo Hospital Lahore from 2010 to 2012. Patients meeting the inclusion criteria were admitted and were treated with Ilizarov external fixator along with necessary soft tissue procedure as required for coverage of exposed bone. There were 30 patients, 15 in each group. Age was between 16 to 60 years. Both groups showed equal frequency of union. The common complications were pin tract infection (predominantly pain) and infection at the fracture site. Excellent functional results were seen in 80%, good in 10% and fair in 10% of the patients. It was concluded that Ilizarov external fixator is an excellent method of fixation for proximal tibial fractures from high-energy trauma with extensive soft tissue damage as it allows management of infection and soft tissue defects and improves limb circulation through early weight bearing.